Literature Review: CRISPR-Cas 9 Genetic Engineering as Breast Cancer Therapy - Salsabila, Pisqiantin Aenan; Bulkis, Nanda; Praditama, Lalu Denendra; Kanata, Nur Ramdhani; Maghfirahandini, Reivirly Khairadaty; Sunarwidhi, Anggit Listyacahyani (Jurnal Biologi Tropis, 2025)
Cancer is a disease characterized by uncontrolled abnormal cell growth, originating from cancer stem cells. These cells form a side population with stemness properties similar to normal stem cells, have high tumorigenicity, and contribute to the development of cancer. Among all cases, breast cancer is one of the causes of cancer death in women worldwide, estimated to reach 28% of new cancers. The application of one of the genetic engineering techniques in the form of CRISPR / Cas9 which can be used as an alternative choice in optimizing breast cancer therapy. This literature review aims to determine CRISPR-Cas 9 Genetic Engineering as Breast Cancer Therapy. This journal review method is through searching for articles from databases such as PubMed, ScienceDirect, and Google Scholar using relevant keywords, namely breast cancer therapy, Genetic Engineering, CRISPR / Cas9 Technique. The results obtained show something promising in the use of one of the genetic engineering technologies in the form of the CRISPR / Cas9 technique which is able to weaken or suppress genetic activity related to the continuity of growth and development of breast cancer cells. In conclusion, CRISPR/Cas9 technology shows promising potential in breast cancer therapy with its ability to inhibit the expression of certain genes that contribute to the growth, invasion, and metastasis of cancer cells.